Morphologic Features of the Distal Femur and Proximal Tibia: A Cross-Sectional Study - Chaurasia, Aditi (Cureus, 2021)
Background The asymmetric medial and lateral condyles of the distal femur and proximal tibia have a direct influence on the biomechanics of knee joint and prostheses design. This study aimed to determine the morphologic data, that is., anteroposterior (AP) and mediolateral (ML) widths, and the radius of curvature (ROC) of the geometric arcs of the distal femur and proximal tibia. Methods One hundred and seventeen adult dry bones (57 femurs and 60 tibias) were studied. Aspect ratios (AP/ML) were calculated. The AP and ML widths were measured using digital Vernier Caliper with a measuring range of 0-150 mm, resolution of 0.01 mm, and accuracy ± 0.02 mm. The geometric arcs of femoral and tibial condyles were divided into three parts namely anterior 1/3rd, distal (femur) or middle (tibia) 1/3rd and posterior 1/3rd and were estimated in the sagittal plane for the femur and transverse plane for tibia using the ROC gauges. Results For the femur, the mean AP length for medial and lateral condyles was 55.62 mm and 57.93 mm, respectively, while the mean ML width was 73.45 mm. For the tibia, the mean AP length for medial condyle (MC) and lateral condyle (LC) was 47.74 mm and 43.46 mm, respectively. The mean aspect ratios for the distal femur and proximal tibia were 1.26 and 1.45, respectively. The mean aspect ratios for MC and LC of the femur were 0.50 and 0.52, respectively, whereas, for tibia, they were 0.61 and 0.71, respectively. The mean ROC for femoral MC - 20.77 mm, 31.42 mm, and 19.68 mm and for LC - 21.48 mm, 64.40 mm and 19.06 mm for the anterior, distal and posterior arcs, respectively. The mean ROC for tibial MC - 22.42 mm, 22.49 mm and 19.94 mm, and LC - 19.92 mm, 21.79 mm and 20.95 mm for the anterior, middle and posterior arcs, respectively. Conclusions The morphologic data accumulated in this study for both the distal femur as well as the proximal tibia would provide guidelines and help the manufacturers of joint prostheses to address the potential for compromised implant fit and re-design and make available ‘anatomic’ knee prostheses appropriate for the local population which would not only improve function but also prolong the longevity of the prostheses.